PENGARUH MEDIA PEMBELAJARAN WORDWALL TERHADAP EFEKTIVITAS, MOTIVASI, DAN MINAT BELAJAR MATERI PECAHAN SISWA KELAS 5 SDN SUKOMORO 2 - Wahyuni, Rizka Tri; Azizah, Nafisyatul; Nugroho, Galuh Eko; Tsaniyah, Siti Muslikhatul; Camarasari, Patriya; Subekti, Hasan (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Wordwall is a web-based interactive learning medium that has the potential to enhance students' motivation, interest, learning outcomes, and technological skills. This research aims to examine the impact of using Wordwall on the effectiveness, motivation, and interest in learning fractions among fifth-grade students from an elementary school in Magetan Regency, East Java. The study employed a descriptive research approach with participants consisting of fifth-grade elementary students in Magetan Regency, East Java. Data were collected by administering questions related to the fractional material taught using Wordwall. The analysis showed that Wordwall demonstrated fairly good effectiveness (72.2%), particularly in students’ understanding (88.9%) and recall of fractional concepts (100%), although their problem-solving speed remained low (33.3%). Student motivation was relatively low (66.7%), with only 55.6% choosing Wordwall and acknowledging its implementation. However, the level of interest was high (100%), indicating that Wordwall successfully captured students’ attention and encouraged active learning. In conclusion, this study found that Wordwall is effective in improving students’ understanding and interest in learning, although its impact on learning motivation was not optimal.